생물학적 동등성 시험을 위한 2×k 교차설계법의 통계적 고려 - 노소영; So Young Noh; 박상규; Sang Gue Park (Ŭngyong tʻonggye yŏnʼgu, 2013)
현재 우리나라 식품의약품안전청에서는 2×2 교차설계법을 기초로 제제간의 생물학적 동등성 평가를 수행하도록 규정하고 있다. 하지만 고변동성 제제의 생물학적 동등성 평가에서 2×2 교차설계법에 의한 시험은 지나치게 많은 피험자를 필요로 할 수 있어 윤리적이고 경제적인 고려가 필요하다는 논의가 이루어지고 있다. 2×2 교차설계법을 대체할 수 있는 대안으로 2×4 교차설계법은 미국 및 유럽 등에서는 생물학적 동등성 평가에 광범위하게 사용되는 설계 방법이고, 2×3 교차설계법도 2×2와 2×4 교차설계법의 단점을 개선할 수 있는 효율적인 대안으로 관심이 많다. 본 연구에서는 2×4와 2×3 교차설계법의 통계적 모형과 제시된 통계적 모형에 연계된 분산분석표를 유도한다. 현행 국내 생물학적 동등성 시험 규정에 의하면 2×4와 2×3 교차설계법의 분산분석표는 반드시 제시되어야 하지만 아직 문헌상에 존재하지 않아 관련 연구에 기여할 것으로 생각된다. 또한 2×4와 2×3 교차설계법에 기초한 피험자 계산을 2×2 교차설계법과 비교 제시하여 고변동성 제제의 생물학적 동등성 시험 연구에 적절한 시험 설계 선택에 정보를 제공한다. The Korea Food and Drug Administration(KFDA) recommends the use of a 2×2 crossover design to assess the bioequivalence of generic drugs. However, a standard 2×2 crossover design for bioequivalence trials is often considered problematic due to ethical and economic issues as highly variable drugs are usually required by large numbers of subjects when designing the trial. To overcome this problem a 2×4 crossover design has been a recommended option as per US regulations; in addition, a 2×3 crossover design has also recently drawn special attention as an efficient alternative. The current KFDA regulation requires an ANOVA table for every bioequivalence study; however, ANOVA tables of 2×4 and 2×3 crossover designs have never been published in the literature. This study shows the derivation of tables of analysis of variance for a 2×4 cross-over design and a 2×3 cross-over design. We also suggest a sample size formulas for 2×2, 2×4 and 2×3 crossover designs to provide information on the selection of efficient designs for highly variable drugs.